2017
DOI: 10.1016/j.meatsci.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of forage-types on the fatty acid profile, lipid and protein oxidation, and retail colour stability of muscles from White Dorper lambs

Abstract: The aim of this study was to evaluate the effect of different forage-types on lamb meat quality parameters. White Dorper lambs that had grazed five forage-types, were slaughtered commercially. At 24h post-mortem, the m. longissimus lumborum (LL) was removed from one side, sliced into three equal sub-samples, vacuum packaged and assigned to ageing periods (5, 12 or 40days); the other side of LL was aged for 5days. The m. adductor femoris was used for fatty acid analysis. Lambs fed chicory+arrowleaf clover had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The results of other authors (Carnevale de Almeida et al, 2006;Mourot et al, 2015;De Brito et al, 2017) suggest that the fatty acid profile, apart from many factors, may be affected by muscle type, regardless of the animal species. The higher content (P < 0.05) of n-6 PUFA in the GM muscle in the present study confirmed the results of Janovska et al (2010), who indicated that muscles with a higher proportion of oxidative fibers have a greater ability to accumulate this family of acids.…”
Section: Lipid Oxidation and Fatty Acid Profilementioning
confidence: 83%
“…The results of other authors (Carnevale de Almeida et al, 2006;Mourot et al, 2015;De Brito et al, 2017) suggest that the fatty acid profile, apart from many factors, may be affected by muscle type, regardless of the animal species. The higher content (P < 0.05) of n-6 PUFA in the GM muscle in the present study confirmed the results of Janovska et al (2010), who indicated that muscles with a higher proportion of oxidative fibers have a greater ability to accumulate this family of acids.…”
Section: Lipid Oxidation and Fatty Acid Profilementioning
confidence: 83%
“…The higher content of PUFA n-6 in GM muscle confirmed the previous results obtained by Janovska et al (2010), indicating the greater capacity of the accumulation of this acid family by muscles with a higher proportion of oxidative fibres, which may be more in GM muscle than in LL. The differences in the content of fatty acids between various muscle types were indicated by Purchas and Zou (2008) in cattle and De Brito et al (2017) in White Dorper lambs.…”
Section: Fatty Acid Profilementioning
confidence: 97%
“…Numerous studies have evaluated the effect of these two contrasting feeding systems on meat flavor and their relationship with levels of fatty acid and volatile compounds [6][7][8][9]. Although the impact that different pasture-based production systems have on lamb meat fatty acid profiles has been characterized [10][11][12][13], less is known about its impact on eating quality. Lamb production in New Zealand is mainly based on grazing systems where various pasture combinations suit different environments across the country.…”
Section: Introductionmentioning
confidence: 99%